The Agility of Agile Methodology for Teaching and Learning Activities - Dewi, Deshinta Arrova; Muniandy, Mohana (2014)
This paper presents the review of literatures that shows the contribution of the agile methodology towards teaching and learning environment at university level. Teaching and learning at university has since migrated from traditional learning to active learning methodology where students are expected to learn by doing rather than listening passively to lectures alone. The agile methodology naturally has promoted the active participation of team members during system development phases. The nature of agile development methodology has been identified as abundantly compatible and supportive towards active academic learning. Some literature have proposed ways of adopting agile into active learning to improve teaching and learning processes and have highlighted this method as a great success. With the review presented in this paper, we would like to highlight how efficient the agile concept is in tackling several situations in academic learning as shown by an interesting mapping of agile principles to the classroom environment. With that, we hope to bring more options to improve active teaching and learning delivery by adopting agile methodology. On the other hand, few papers have used the academic environment to measure the agile principles. By highlighting this, we offer options for the agile evaluation framework to consider academic environment as a tool to obtain the agile performance feedback.